2000
DOI: 10.1074/jbc.m000540200
|View full text |Cite
|
Sign up to set email alerts
|

Dual Regulation of Platelet Protein Kinase B

Abstract: Protein kinase B (PKB) is a serine/threonine kinase that is activated by growth hormones and implicated in prevention of apoptosis, glycogen metabolism, and glucose uptake. A key enzyme in PKB activation is phosphatidylinositide 3-kinase (PI-3K), which triggers the dual phosphorylation of PKB by phosphatidylinositol-dependent kinases (PDKs). Here we report that the major PKB subtype in platelets is PKBalpha, which is activated by phosphorylation of Thr(308) and Ser(473) and has a constitutively phosphorylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
148
2
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(163 citation statements)
references
References 42 publications
11
148
2
2
Order By: Relevance
“…In thrombin-treated platelets, a conventional PKC inhibitor also prevented pAktS473, although the effect was only partial and a co-factor was probably necessary. 40 Because our activity assays were performed with PKC-␤1 immunoprecipitated from MC under various conditions, we cannot exclude requirement for a co-factor when PKC-␤1 functions as an AktS473 kinase.…”
Section: Discussionmentioning
confidence: 99%
“…In thrombin-treated platelets, a conventional PKC inhibitor also prevented pAktS473, although the effect was only partial and a co-factor was probably necessary. 40 Because our activity assays were performed with PKC-␤1 immunoprecipitated from MC under various conditions, we cannot exclude requirement for a co-factor when PKC-␤1 functions as an AktS473 kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Balendran et al [29] have shown that 3-phosphoinositide-dependent protein kinase-1, Akt and protein-kinase-C-related kinase-2 interact with each other after the phosphorylation of Thr308, which can be converted into 3-phosphoinositide-dependent protein kinase-2 (PDK2) and modify Ser473. Kroner et al [30] have found that the existence of PDK2 can be proven by the complex relationship between Thr308 and Ser473, which is phosphorylated independently. A study by Ferguson et al [31] has shown that Akt can be activated in a PI3-K-independent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…ILK is a viable candidate because depletion of ILK in HEK-293 cells with the use of siRNA almost completely inhibits Ser 473 phosphorylation (24), although it is presently unknown whether ILK exerts these effects directly or via an intermediate kinase. Finally, in platelets, activation of PKC can phosphorylate Akt on Ser 473 in a PI3-K-independent manner (14). This is unlikely to be the case in VSMCs, however, because ANG II-induced activation of Akt is PI3-K-dependent (26), as it is for most other agonists and cell types (15).…”
Section: Discussionmentioning
confidence: 99%